Pengaruh Product Quality, Brand Image dan Customer Satisfaction terhadap Customer Loyalty Product Skincare - Sophiyanto Wuryan; Safira Mei Anindita (Lembaga Yasin AlSys, 2026)
Customer loyalty is an indicator of a company’s success in maintaining customer satisfaction, which in the skincare industry is strongly influenced by product quality and brand image, while empirical studies that specifically integrate Product Quality, Brand Image, and Customer Satisfaction as determinants of consumer loyalty to skincare products in urban areas of Indonesia remain relatively limited. This study aimed to analyze the influence of Product Quality, Brand Image, and Customer Satisfaction on Customer Loyalty among users of Skintific skincare products in Jakarta and Bekasi. A quantitative approach with a survey design was employed, involving 100 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The results showed that Product Quality and Brand Image had a significant effect on Customer Satisfaction, while Customer Satisfaction and Brand Image directly contributed to increasing Customer Loyalty. These findings confirm that customer satisfaction functions as a key variable in shaping consumer loyalty, whereas brand image strengthens the long-term relationship between customers and the company. This study contributes to the development of understanding of consumer behavior in the beauty industry and offers practical implications for skincare companies in designing strategies to improve product quality, strengthen brand image, and manage customer satisfaction on an ongoing basis, while also opening opportunities for further research by expanding the variables and geographical coverage to obtain stronger generalizations of the findings.